(untitled) (International Conference on Education, Psychology and Humanities, 2026)
Pragmatic competence has become, especially in the last few decades, one of the issues that attracted attention in the field as an essential part of language competence. The realization that having a good command of linguistic knowledge in target language would not be enough to master the language has created the need to investigate the value and effect of pragmatic competence in language education. This work is intended to provide a brief overview of pragmatics and pragmatic competence, the pedagogic significance of pragmatic competence highlighting the relevant theoretical components of pragmatics. For the purposes of my work, relevant literature covering definitions of pragmatics and pragmatic competence and research carried out on pragmatic competence is presented.